Why Has Japan Been Hit So Hard by the Global Recession? - Sommer, Martin (Washington, D.C. : International Monetary Fund, 2009)
The Japanese economy has been hit hard by the slump in global demand for advanced manufacturing products such as cars, information technology, and machinery, which account for a larger share of production than in other G-7 economies. Most of the drop in Japan's exports was caused by a sharp retrenchment in overseas demand for motor vehicles, information technology, and capital goods, as firms and consumers cut their investment and durable goods spending in response to the global credit crunch and extraordinary uncertainties about the outlook. Worsening domestic financial conditions deepened the current recession by reducing domestic demand, especially business investment. The short-term outlook is further clouded by the needed adjustment to inventories, which have accumulated well above normal levels in both Japan and its export markets. During the 2001 recession, industrial production started recovering about 5 months after the peak of the inventory cycle. By analogy, one could expect a bottom in industrial production around May 2009. However, since the global environment is expected to remain weak and the Japanese economy faces headwinds from tight domestic financial conditions, the production adjustment could take longer during this recession.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Condition; Inventory Adjustment; Inventory; SPN; Japan